2016
DOI: 10.1016/j.jpain.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Sleep Quality Deteriorates Before Development of Painful Temporomandibular Disorder

Abstract: There is good evidence that poor sleep quality increases risk of painful temporomandibular disorder (TMD). However little is known about the course of sleep quality in the months preceding TMD onset, and whether the relationship is mediated by heightened sensitivity to pain. The Pittsburgh Sleep Quality Index was administered at enrollment into the OPPERA prospective cohort study. Thereafter the Sleep Quality Numeric Rating Scale was administered every three months to 2,453 participants. Sensitivity to experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 38 publications
2
76
0
1
Order By: Relevance
“…28 However, perceived stress was shown to mediate the link between the PSQI and TMD onset, while the PSQI did not mediate the role of stress in TMD development. 29 Similarly, our findings underscore the importance of psychological variables in the PSQI-TMD relationship and suggest that differences in the baseline PSQI and subsequent sleep ratings preceding the TMD onset 28,29 may not reflect differences in PSG-measured sleep parameters but represent negative cognitive bias and depressive symptomatology.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…28 However, perceived stress was shown to mediate the link between the PSQI and TMD onset, while the PSQI did not mediate the role of stress in TMD development. 29 Similarly, our findings underscore the importance of psychological variables in the PSQI-TMD relationship and suggest that differences in the baseline PSQI and subsequent sleep ratings preceding the TMD onset 28,29 may not reflect differences in PSG-measured sleep parameters but represent negative cognitive bias and depressive symptomatology.…”
Section: Discussionmentioning
confidence: 94%
“…A large longitudinal study assessing risk factors for the development of TMD revealed that the elevated PSQI and the subsequent reduction in subjective sleep quality predict future onset of TMD independently of stress or comorbid conditions (28). However, perceived stress was shown to mediate the link between the PSQI and TMD onset, while the PSQI did not mediate the role of stress in TMD development (29).…”
Section: Zero-order Correlationsmentioning
confidence: 99%
“…In contrast, sleep quality remained stable among participants who did not develop TMD. 45 That analysis had investigated whether the putative effect of sleep quality was mediated by increased sensitivity to experimental pain, but found no evidence of such mediation. 45 Because of the overlap and temporal ambiguity between sleep disturbance, perceived stress, and pain, it is not surprisingly that different causal configurations have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…45 That analysis had investigated whether the putative effect of sleep quality was mediated by increased sensitivity to experimental pain, but found no evidence of such mediation. 45 Because of the overlap and temporal ambiguity between sleep disturbance, perceived stress, and pain, it is not surprisingly that different causal configurations have been proposed. For example, in a study of persistent pain nested within the prospective North Staffordshire Osteoarthritis Project, investigators reported that pain interference mediated the effect of sleep disturbance on probable depression, as well as the effect of probable depression on sleep disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Another requirement was that individuals be reliably and unambiguously classified into meaningful categories based on their risk profiles. The method Sanders et al (2016). Sleep quality was rated on a scale of 0 to 10 (0 = worst sleep, 10 = best sleep) in questionnaires completed once every quarter during follow-up of first-onset TMD cases (n = 220) and controls (n = 193) in the OPPERA nested case-control study.…”
Section: Putting It All Together: Finding the Forest Among The Treesmentioning
confidence: 99%